Coleridge's philosophies - Halmi, N (Cambridge University Press, 2022)
This new collection enables students and general readers to appreciate Coleridge’s renewed relevance 250 years after his birth. An indispensable guide to his writing for twenty-first-century readers, it contains new perspectives that reframe his work in relation to slavery, race, war, post-traumatic stress disorder and ecological crisis. Through detailed engagement with Coleridge’s pioneering poetry, the reader is invited to explore fundamental questions on themes ranging from nature and trauma to gender and sexuality. Essays by leading Coleridge scholars analyse and render accessible his extraordinarily innovative thinking about dreams, psychoanalysis, genius and symbolism. Coleridge is often a direct and gripping writer, yet he is also elusive and diverse. This Companion’s great achievement is to offer a one-volume entry point into his incomparably rich and varied world.